Education 2.0: The Learning Web Revolution and the Transformation of the School - Dahl, Audrey (Canadian Journal of Education/Revue canadienne de l'éducation, 2015)
Education 2.0: The Learning Web Revolution and the Transformation of the School Par L. J. Waks Boulder, CO: Paradigm Publishers, 2013, 256 pages. ISBN: 978-1-61205-036-2 (PB)